PERFORMANCE OF CONVENTIONAL, ISLAMIC, AND SOCIAL RESPONSIBLE INVESTMENT (SRI) INDICES DURING COVID-19: A STUDY OF INDONESIAN STOCK MARKET - Hidayah, Nur; Swastika, Putri (Bank Indonesia, 2022)
This paper investigates (i) the volatility of Indonesian Islamic, SRI, and Conventional equities, (ii) their serial correlation, and (iii) their dynamic correlation and relationship during the COVID-19 pandemic. Using MGARCH-DCC, our findings suggest that the Islamic index is most volatile but performs more efficiently than the others and exhibits no co-movement with Conventional and SRI during the Pandemic crisis. The study empirically shows the resilience and efficiency of the Islamic stocks in Indonesia during the Pandemic. These findings provide valuable and practical recommendations on portfolio diversification for investors and offers policy implications for regulators interesting in and dealing with impact or responsible investing. Acknowledgment The authors would like to thank KNEKS for the academic writing workshop series that made this study possible.